DEVELOPMENT OF AUDIO-VISUAL-BASED LISTENING TEACHING MATERIALS USING YOUTUBE APPLICATION IN GRADE EIGHT STUDENTS OF SMP NEGERI 15 MEDAN - Risnawaty, Defy Gita Aurora (Jurnal Review Pendidikan dan Pengajaran, 2024)
This research aims to determine the effectiveness of the development of listening teaching materials from conventional methods or using books into audio-visual-based teaching materials using the YouTube application and also to describe validation from experts about the development of audio-visual-based listening teaching materials using YouTube application, especially in the environment of SMP Negeri 15 Medan. Data collection instruments in the form of tests and questionnaires. This research uses a development method using the ADDIE model as the basis, based on the research data obtained, it can be ascertained that the results of this research are by the initial goal, namely the development of the distance learning system, this is evidenced by the increase in the value of students. Based on the results of this study the author can conclude that the research conducted is considered successful. This is determined by the author based on comparing students' ability when testing based on pre-test and post-test. The results of this study are shown by the ability of students who previously got material using books as a reference have developed compared to before getting the presentation of material with video media using the YouTube application. The author also concluded that the lack of interest in reading students can be diverted using video-based material to increase the interest students. The importance of the role of educational institutions in providing training to teachers related to information and technology-based learning methods and preparing guidelines and learning plans that are systematic, clear and directed as guidelines for teachers and students in applying online learning methods, especially using YouTube.